Perlindungan Hukum Tanah Ulayat Terhadap Perjanjian Hak Pakai Atas Tanah di Batipuh Kabupaten Tanah Datar - Indri, Anggelina; Irianto, Kartika Dewi (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
This study aims to examine the forms of legal protection for tanah ulayat (customary communal land) utilized through hak pakai (right of use) agreements in the Batipuh area, Tanah Datar Regency, West Sumatra. In the context of Minangkabau customary law, tanah ulayat is a collective asset owned by a kaum (clan) or suku (tribe) and cannot be sold. However, in practice, many hak pakai agreements are conducted orally without formal documentation, which poses the risk of legal disputes and weakens the position of indigenous communities. This research employs an empirical juridical method, using sociological and customary law approaches, supported by field data obtained through interviews with the Kerapatan Adat Nagari (KAN), Wali Nagari (village head), and local government officials. The findings reveal that although oral agreements are recognized under customary law as a valid form of consensus, they lack evidentiary strength before the state legal system. The absence of written documentation weakens the legal standing of indigenous communities in cases of breach of contract or violations by land users. The KAN and Wali Nagari function as moral guardians and mediators in disputes but have no formal authority to enforce state law. To strengthen legal protection for tanah ulayat, it is essential to integrate customary law and state law through the legalization of customary agreements in written form, without undermining the principles of consensus and deliberation (musyawarah dan mufakat). Local regulatory reforms and the capacity building of customary institutions are key to ensuring the protection of indigenous peoples’ rights over tanah ulayat now and in the future.